Effect of inspiratory muscle training with threshold valve on functional capacity of physically active women who are older than 60 years of age - Espinoza-Salinas, Alexis; Arenas-Sanchez, Giovanny; Fernández-García, Roberto; Ravanales-Astudillo, Omar; González-Jurado, José; Zafra-Santos, Edson (Universidad y Salud, 2019)
Introduction: Physiological changes associated with aging generate a series of functional modifications, mainly a decrease in respiratory capacity. In this regard, an alternative strategy to improve such a condition could be inspiratory muscle training (IMT). Objective: To analyze the effect of IMT with threshold valve on the functional capacity of physically active women who are older than 60 years of age. Materials and methods: IMT with threshold valve was carried out over a period of 4 weeks, comparing data from the experimental group (GE; n:10) to the control group (GC; n:5). The following hemodynamic and anthropometric variables were assessed: weight, height, body mass index (BMI), lactate, double product (DP) and functional capacity. Pre and post training changes were evaluated. Results: The GE group showed a decrease in both post-intervention lactate concentration (from 3.16±0.51 to 2.5±0.39) and effort perception scale (from 5.56 ± 1.81 to 4±2). On the other hand, this group experienced a post-intervention increase in maximal inspiratory pressure (MIP) from 42.11±14.57 to 60.44±14.47. The GC group did not present changes in its values. Conclusion: Although no evidence was found regarding favorable changes in the walked distance post-intervention, IMT induced a reduction in post-exercise lactate concentration, which could indicate a delay of onset of fatigue.